Highly reliable lead-free solder alloy for harsh operating conditions

JP7630436B2Active Publication Date: 2025-02-17ジ·インジウム·コーポレーション·オブ·アメリカ
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2021549601
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-02-26
Filing Date
2020-02-26
Publication Date
2025-02-17
Estimated Expiration
2040-02-26

Smart Images

  • Figure 0007630436000001
    Figure 0007630436000001
  • Figure 0007630436000002
    Figure 0007630436000002
  • Figure 0007630436000003
    Figure 0007630436000003
Patent Text Reader

Abstract

A high-reliability lead-free solder alloy for severe use conditions is disclosed. In some embodiments, the solder alloy comprises 2.5-4.0 wt.% Ag; 0.4-0.8 wt.% Cu; 5.0-9.0 wt.% Sb; 1.5-3.5 wt.% Bi; 0.05-0.35 wt.% Ni; and the balance being Sn. In some embodiments, an apparatus includes a component including a main ceramic body and a side surface on which electrodes and thermal pads are disposed; a copper substrate; and a solder alloy electrically connecting the component and the copper substrate, the solder alloy comprising 2.5-4.0 wt.% Ag; 0.4-0.8 wt.% Cu; 5.0-9.0 wt.% Sb; 1.5-3.5 wt.% Bi; 0.05-0.35 wt.% Ni; and the balance being Sn. In some embodiments, an apparatus includes a light-emitting diode (LED) component; a metal core printed circuit board (MCPCB); and a solder alloy electrically coupling the LED component and the MCPCB, the solder alloy including 2.5-4.0 wt.% Ag; 0.4-0.8 wt.% Cu; 5.0-9.0 wt.% Sb; 1.5-3.5 wt.% Bi; 0.05-0.35 wt.% Ni; and the balance Sn.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims priority to U.S. Provisional Patent Application No. 62 / 810,619, entitled "High Reliability Leadfree Solder Alloys for Harsh Service Conditions," filed February 26, 2019, the disclosure of which is incorporated herein by reference in its entirety.

[0002] The disclosed technology relates generally to solder alloys, and more particularly, some embodiments relate to lead-free solder alloys. [Brief description of the drawings]

[0003] The present disclosure, in accordance with one or more various embodiments, will now be described in detail with reference to the following figures, in which: The drawings are provided for purposes of illustration only and merely depict typical or exemplary embodiments.

[0004] 1-3 show the assembly of an LED module comprising an LED electrically coupled to a metal core printed circuit board (MCPCB) by solder according to an embodiment of the disclosed technology.

[0005] [Figure 1] FIG. 2 is a diagram showing the bottom surface of an LED.

[0006] [Diagram 2] FIG. 2 is a view showing the top surface of the MCPCB.

[0007] [Diagram 3] FIG. 2 shows a completed LED module.

[0008] [Figure 4] FIG. 1 illustrates a system for testing LED modules when assembled using different solder alloys according to a power cycling reliability test.

[0009] [Diagram 5] FIG. 1 is a box plot of data collected during testing of several solder alloys.

[0010] [Figure 6] 1 is a plot showing the percentage of failed LED modules versus cycles to failure.

[0011] [Figure 7] FIG. 2 is a cross-sectional view of an LED module before a power cycle reliability test.

[0012] [Figure 8] FIG. 1C is a cross-sectional view of an LED module using Alloy 20 solder paste after failure during power cycling reliability testing.

[0013] [Figure 9] FIG. 13 shows similar images for Alloy 11.

[0014] [Figure 10] FIG. 1 shows the chemical composition and melting behavior of various disclosed solder alloys and comparative novel solder alloys.

[0015] [Figure 11-13] 11-13 are cross-sectional views of two samples of Alloys 25 and 6, respectively, during thermal cycle testing from -40°C to +150°C.

[0016] [Figure 11] FIG. 1 shows alloys at 1839 cycles.

[0017] [Figure 12] FIG. 1 shows alloys at 2565 cycles.

[0018] [Figure 13] FIG. 1 shows alloys at 3012 cycles.

[0019] [Figure 14] FIG. 13 is a diagram showing statistical data of chip resistors that failed after 3000 cycles of thermal cycling (−40° C. to +150° C.).

[0020] [Figure 15] FIG. 13 is a diagram showing statistical data of chip resistors that failed after 6000 cycles of thermal cycling (−40° C. to +150° C.).

[0021] The drawings are not exhaustive and are not intended to limit the disclosure to the precise forms disclosed. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0022] The embodiments disclosed herein provide an innovative Sn-Ag-Cu-Sb based lead-free solder alloy for electronics applications in harsh environments. The solder alloy can be used in applications such as printed circuit board (PCB) level assembly for component solder interconnection, high brightness light emitting diode (LED) chip bonding on Cu, Al or other substrates and metal core PCBs, and semiconductor die attach for power modules. The solder alloy may include additives selected from 1.0-3.5 wt% Bi and / or 0.1-1.0 wt% In. Additionally, the solder alloy may contain 0.05-0.35 wt% Ni.

[0023] Lead-free solder alloys have been widely adopted in the electronics industry since July 2006, when the Restriction on Hazardous Substances (RoHS) regulation was implemented in the European Union. Over the past decade, lead-free SnAgCu ("SAC") solder alloys such as Sn3.0Ag0.5Cu (SAC305) and Sn3.8Ag0.7Cu (SAC387) have been widely used in portable, computing, and mobile electronics with operating temperature ranges of 125°C or less. Emerging automotive electronics are requiring operating temperatures of around 150°C for devices used under the hood, while the 125°C or less requirement is likely to remain for devices in the passenger compartment. Beyond the maximum operating temperature, automotive electronics are also required to function over a wide temperature range, from as low as -40°C to +150°C or even higher.

[0024] In such harsh electronics environments, conventional binary or ternary lead-free high Sn solder alloys are not reliable enough to survive. For the melting temperatures of most high Sn solders, the homogeneous temperatures at 150°C are equal to 0.876 for SnAgCu-3Bi, 0.863 for SnAgCu, 0.856 for Sn-3.5Ag, and 0.846 for Sn-0.7Cu, indicating that atomic diffusion significantly promotes microstructural development and accelerates joint degradation. The higher the operating temperature, the more quickly microstructural coarsening and joint degradation occurs. The disclosed high reliability solders for higher service temperature applications reflect metallurgical design considerations to retard the microstructural development and growth of interfacial intermetallic compounds (IMCs) in the joint solder body, resulting from atomic diffusion under thermomigration.

[0025] In addition to temperature, automotive electronics need to withstand continuous vibration or even mechanical shock during vehicle movement and braking. Ductile joints are desirable for improved vibration / shock resistance. However, the growth of interfacial IMCs and coarsening of the microstructure make the joint more brittle, especially at elevated temperatures. It is therefore desirable not only to engineer the joint to be ductile, but also to maintain the ductility of the joint during operation under harsh conditions from a metallurgical point of view.

[0026] Beyond the harsh use environments of automotive electronics, high-temperature and high-reliability high-Sn solders can be used for high-brightness (HB) LED chip component assembly and die attach in power semiconductor modules where subsequent board-level reflow is not required. For power semiconductor modules, Joule heat from the applied current raises the bond junction temperature to 150°C or even higher, depending on the module design. Assuming that the heat dissipation method remains the same, the higher the current density, the higher the junction temperature. The high current density of HB-LEDs heats the junction junctions (both anode and cathode junctions, as well as the thermal pad junction between the two electrodes) to 150°C or even higher, similar to power semiconductor modules, depending on the current and cooling pad design. However, high-power devices, including both HB-LEDs and power modules, can stress bond junctions not only with high junction temperatures, but also with high current densities. Thus, embodiments of high-reliability solder designs for power applications can reduce atomic diffusion under electromigration and control atomic diffusion under thermomigration.

[0027] To address the need for solder materials for both the automotive industry and power semiconductor applications, the disclosed novel metallurgical design for high reliability lead-free solder embodiments focuses on stabilizing the microstructural development and slowing down the growth of interfacial IMCs under both thermal and current stress conditions.

[0028] The embodiments disclosed herein include lead-free solder alloys comprising 2.5-4.0 wt% Ag; 0.4-0.8 wt% Cu; 5.0-9.0 wt% Sb; 1.5-3.5 wt% Bi; 0.1-3.0 wt% In; 0.05-0.35 wt% Ni; and balance Sn. These disclosed solder alloys have excellent thermal fatigue resistance in harsh service environments requiring high reliability at operating temperatures of 150°C or higher. Solders within the claimed range have longer characteristic life than conventional binary and ternary high Sn solders for HB-LED chip bonding and die attach in board level automotive applications, as well as power semiconductor module applications. The solder alloys of the present invention are particularly suitable for producing solder joints in the form of, for example, but not limited to, solder preforms, solder balls, solder powders, solder pastes (mixtures of solder powder and flux), and the like.

[0029] FIG. 10 shows the chemical composition and melting behavior of various disclosed solder alloys (Alloy Nos. 1-16) and comparative solder alloys (Alloy Nos. 17-25). The melting behavior of the solder alloys was analyzed using differential scanning calorimetry (DSC) at the same heating and cooling rates of 20°C / min. DSC tests were performed in a TA Q2000 differential scanning calorimeter, scanning from room temperature to 280°C. For each alloy, the sample was first scanned from ambient temperature to 280°C, followed by cooling to 25°C, and then scanned again to 280°C. A second heating thermograph was used to represent the melting behavior of the alloys. The solidus and liquidus temperatures of the solder alloys obtained from the DSC analysis are listed in FIG. 10.

[0030] In some embodiments, Sb plays an important role in improving the thermal fatigue resistance of solder joints under severe thermal cycle or thermal shock conditions. In such embodiments, 5.0 wt% to 9.0 wt% Sb is added to maintain an optimized volume fraction of fine SnSb intermetallic compound (IMC) particles. The fine SnSb IMC particles nucleate and grow (clusters of different atoms with a certain stoichiometric ratio) after solder solidification during reflow. These SnSb particles back dissolve in the Sn matrix to form a solid solution as the temperature increases, and then precipitate as the temperature decreases. A sufficient amount of Sb is important to harden the solder alloy by providing both solid solution and precipitation strengthening to the alloy. When the amount of Sb is reduced below 3.0 wt%, the SnSb particles completely dissolve in the Sn matrix to form a (SnSb) solid solution at 150°C or higher, and no SnSb particles remain to strengthen the alloy. The strengthening of the alloy is associated with the impediment of dislocation motion. Both the fine particles embedded in the alloy matrix and the solute atoms in solid solution act as obstacles to prevent dislocations from gliding along the preferred lattice direction. At high temperatures (homogenous temperature >0.6), atomic diffusion plays an important role in aiding dislocation motion. For small obstacles such as solute atoms, atomic diffusion can easily help dislocations to bypass or overcome the obstacles. For larger obstacles such as precipitates, more atomic diffusion steps are needed to allow dislocations to bypass or overcome the obstacles. Thus, precipitates are more beneficial to maintain high temperature strength by hindering dislocation motion. In the present invention, 5 wt% or more Sb allows sufficient precipitate strengthening even at 150°C or higher. However, when the addition of Sb exceeds 10 wt%, coarse and brittle Sn particles form during solidification. 3 Sb 2 A major phase forms in the solder, making the solder alloy much more brittle. Sn 3 Sb 2Embrittlement due to the Sb phase tends to cause premature failure of solder joints under severe thermal cycling or thermal shock conditions. Therefore, in some embodiments, the Sb content is more preferably in the range of 5.0-9.0 wt.% (optimally 5.0-6.5 wt.%) to maintain a balanced strengthening effect.

[0031] Ag acts as a dispersion strengthening phase. 3 It acts as a main strengthening element in the alloy by forming Sn intermetallic compound particles. Ag also improves the wettability of the solder alloy. Considering the comprehensive performance including melting, wetting, mechanical properties and thermal cycle reliability, the Ag content is preferably in the range of 2.5-4.5 wt%. When Ag is less than 2.5 wt%, the mechanical properties and thermal cycle reliability performance of the solder joints are inferior to those of the unsatisfactory Ag content. 3 Due to Sn particles, it may not be sufficient for harsh environment electronics applications. When Ag exceeds 4.5 wt%, the liquidus temperature of the alloy increases significantly, and Ag is added instead of the particles. 3 The formation of Sn platelets may reduce the ductility of the solder joint. Furthermore, a higher Ag content is undesirable because it increases the cost. Therefore, in some embodiments, the Ag content is preferably in the range of 3.0 to 4.0 wt.%.

[0032] Cu is one of the main constituent elements and is embedded in the solder matrix. 6 Sn 5 It improves the mechanical properties of the solder by forming intermetallic particles. With sufficient Cu in the molten solder, Cu leaching from the Cu substrate metal or Cu pad is also significantly reduced. In addition, high Cu content in the solder can cause brittle Ni metallization on the Ni metallization surface. 3 Sn 4 Not ductile (Cu,Ni) 6 Sn 5 The high Cu content in the solder can stabilize the interfacial intermetallic compound layer by forming a double IMC layer on the Ni metallization surface, i.e. (Cu,Ni) 6 Sn5 (Cu,Ni) formed under 3 Sn 4 The formation of voids can also be prevented. In general, the double IMC layer actually weakens the bonding interface. However, when Cu exceeds 2.0 wt%, the pasty range becomes too wide, which affects the wettability, voids and reliability of the solder. Therefore, in some embodiments, the Cu content is preferably within the range of 0.4-1.0 wt%.

[0033] As an additive to SnAgCuSb alloys, Bi can reduce the solidus and liquidus temperatures of the alloy, and accordingly reduce the reflow peak temperature. Bi also reduces the surface tension of the molten solder, thus improving wettability. Bi does not form IMC precipitates with Ag, Cu, Sb, and Sn. Bi strengthens the solder body with Bi particles at low temperatures, and forms a solid solution at high temperatures to harden the solder body. Because Bi is brittle, when Bi is added in excess of 4 wt%, the strength continues to increase, but the ductility decreases significantly. This embrittlement significantly deteriorates the thermal fatigue resistance. Bi continuously reduces the melting temperature with increasing content in the solder, and even forms a low-melting Bi-Sn phase, which is undesirable for high-temperature high-reliability applications. In some embodiments, a Bi addition of 1.5 to 3.5 wt% is preferred for electronic equipment applications in harsh environments.

[0034] Like Bi, In also lowers the solidus and liquidus temperatures of the solder. In is much softer than Bi and Sb, which helps increase ductility and reduces the brittleness introduced by the Bi and Sb additions. In the disclosed embodiment, where 1.5-3.5 wt.% Bi and 5-9 wt.% Sb are added to improve the wetting and strength of the solder alloy, by simultaneously employing sufficient In, the brittleness introduced by the Bi and Sb additions is minimized. In has similar IMC formation effects as Sn, i.e., Ag. 3 (SnIn), Cu 6 (SnIn) 5 , Ni 3 (SnIn)4 , and even (CuNi) 6 (SnIn) 5 etc. The complex IMC structure slows down the coarsening and thickening of the IMC at high temperatures (which requires more atoms to diffuse towards the IMC to support the growth). This stabilizes the IMC and subsequently helps strengthen the precipitates, mitigating the growth of the IMC and the associated joint embrittlement. However, In is more easily oxidized than Bi, and the addition of more than 4.5 wt% In to the solder significantly reduces the wettability during reflow and increases voids. Therefore, in some embodiments, an In addition of 4.5 wt% or less is preferred. The preferred In content in the alloy also depends on the Sb content. The In addition dramatically reduces the melting temperature. To maintain the high temperature performance of the joint, the In addition is preferably less than 3.0 wt% to avoid the formation of these low initial melting phases in the alloy.

[0035] In some embodiments, 0.05-0.35 wt.% Ni is added to further improve the mechanical properties of the alloy and the reliability performance of the solder joints. During soldering, there is enough Ni to participate in the interfacial IMC formation, especially in Cu metallization, to allow the Cu to 6 Sn 5 Instead of (CuNi) 6 Sn 5 is formed. (CuNi) 6 Sn 5The presence of Ni in the layer slows down IMC growth during reflow and post-reflow use, which is important for maintaining interfacial stability and ductility of the joint. Ni has very limited solubility in Sn. Above 0.4 wt% Ni, the liquidus temperature of the solder increases dramatically. A negative effect on wettability and solderability with more than 0.4 wt% Ni, along with Ni's reactivity to oxidation, is seen, especially for fine powder solder pastes. Thus, the upper limit of Ni addition is preferably 0.35 wt% in various embodiments. On the other hand, interfacial IMC stabilization is marginal due to insufficient Ni participation in the interfacial reaction at Ni contents below 0.05 wt%. Thus, in some embodiments, 0.05-0.35 wt% Ni is preferred.

[0036] Alloys designed within the disclosed technology have been tested for board level assembly, HB-LED applications, and power semiconductor module applications. Significant improvements have been achieved compared to conventional Sn-Ag, Sn-Cu, and Sn-Ag-Cu alloys. For example, HB-LED power cycling tests show up to a three-fold increase in characteristic time compared to conventional SAC305 (alloy 25), from 3893 cycles to 11960 cycles (alloy 13).

[0037] 1-3 show the assembly of an LED module with LEDs electrically coupled to a metal core printed circuit board (MCPCB) by solder according to an embodiment of the disclosed technology. FIG. 1 shows the bottom side of an LED 100. The bottom side includes three solder pads. One of the solder pads is a thermal pad 104, and the other two solder pads 106 are for the electrodes of the LED 100. FIG. 2 shows the top side of an MCPCB 200. Three solder pads with metallization 206 are disposed on the top side of the MCPCB 200. These solder pads 206 correspond to the solder pads 104 of the LED 100. FIG. 3 shows a completed LED module 300, with the LED 100 bonded to the MCPCB 200 and wires 302 bonded to the MCPCB 200.

[0038] FIG. 4 shows a system 400 for testing LED modules 300 when assembled using different solder alloys according to a power cycling reliability test. The system 400 includes a direct current (DC) power supply 402 connected to the wires 302 of the LED module 300 and a data collection unit 404 for collecting test data. During testing, each LED module was power cycled until failure. Each cycle included application of power for 8 seconds followed by no power application for 20 seconds. FIG. 5 shows a box plot 500 of data collected during testing of multiple solder alloys. FIG. 6 is a plot showing the percentage of failed LED modules versus the number of cycles to failure. From FIG. 5 and FIG. 6, it can be seen that alloys 4, 11, and 12 have longer characteristic lifetimes than other alloys, especially alloys 18-21, which do not have Ni addition. The results show that Ni addition to the solder alloy is beneficial in improving the lifetime of LED devices.

[0039] 7 shows a cross-sectional view of an LED module 700 before power cycling reliability testing. The electrodes of the LED module 700 are indicated at 706a,b. The thermal pads are indicated at 704. The MCPCB is indicated at 710. The solder paste is indicated at 708.

[0040] FIG. 8 shows a cross-sectional view of an LED module 800 using Alloy 20 solder paste after failure during power cycling reliability testing. Referring to FIG. 8, significant cracks and Cu 6 Sn 5 A significant growth of SiO2 can be seen. A top view radiographic image is shown in the bottom center of Figure 8. Figure 9 shows a similar image for alloy 11. These radiographic images show the circular voids (white) in the LED device.

[0041] Board-level reliability under harsh environments was also evaluated for these alloys. Solder pastes were mixed using the solder alloy powders shown in Figure 10 along with flux. The solder pastes were then tested on both chip resistor and ball grid array (BGA) assemblies under harsh thermal cycling conditions from -40°C to +150°C.

[0042] Figures 11-13 are cross-sectional views of two samples of alloys 25 and 6, respectively, during thermal cycling tests from -40°C to +150°C. Figure 11 shows the alloy at 1839 cycles. Figure 12 shows the alloy at 2565 cycles. Figure 13 shows the alloy at 3012 cycles. From these images, it can be seen that the disclosed alloy 6 exhibits significantly improved crack resistance over the conventional alloy 25 (SAC305).

[0043] FIG. 14 shows the statistical data of chip resistors that failed after 3000 cycles of thermal cycling (-40°C to +150°C). FIG. 15 shows the statistical data of chip resistors that failed after 6000 cycles of thermal cycling (-40°C to +150°C). Each row in these tables represents the testing of 60 resistors. The fluxes in the "Flux" column are labeled A for Indium8.9HF, B for Indium10.1HF, and C for Indium3.2HF, all of which are commercially available. The resistors in the "Chip Resistor Type" column are listed by package part number.

[0044] It is clear that the disclosed alloys 6 and 11 performed better than the comparative alloys, such as alloys 21, 24 and 25. The data also show that the choice of flux affects the reliability of the solder joints.

[0045] Embodiments have also been tested on power module packages with Si die bonded onto ceramic substrates. The characteristic life of the packages under thermal cycling from -40°C to 175°C shows a much slower degradation of bond joint strength compared to conventional SAC305 alloy.

[0046] Although various embodiments of the disclosed technology have been described above, it should be understood that they are presented only as examples and not as limitations. Although the disclosed technology has been described above with respect to various exemplary embodiments and implementations, it should be understood that the various features, aspects and functions described in one or more of the individual embodiments are not limited in their applicability to the particular embodiment described, but instead can be applied alone or in various combinations to one or more of the other embodiments of the disclosed technology, regardless of whether such an embodiment is described and whether such features are presented as part of the described embodiment. Thus, the breadth and scope of the technology disclosed herein should not be limited by any of the exemplary embodiments described above.

[0047] The terms and phrases used herein, and variations thereof, unless expressly stated otherwise, should be interpreted as open-ended rather than limiting. As examples of the above, the term "including" should be read as meaning "including, but not limited to" and the like; the term "example" is used to provide illustrative examples of the items under discussion, rather than an exhaustive or limiting list thereof; the term "a" or "an" should be read as meaning "at least one", "one or more", and the like; adjectives such as "conventional", "conventional", "normal", "standard", "known" and the like and terms of similar meaning should not be interpreted as limiting the described items to those available during a given period or at a given time, but instead should be read to encompass conventional, conventional, normal, or standard technology that may be available or known at any time now or in the future. Similarly, when the present specification refers to technology that is obvious or known to a person skilled in the art, such technology encompasses technology that is obvious or known to a person skilled in the art at any time now or in the future.

[0048] In some cases, the presence of broad words and phrases such as "one or more," "at least," "including but not limited to," or other similar phrases should not be construed to imply that a narrower case is intended or required in the absence of such broad phrases. Use of the term "module" does not imply that components or functionality described or claimed as part of a module are all configured within a common package. Indeed, any or all of the various components of a module, whether control logic or other components, may be combined into a single package or maintained separately, and may even be distributed into multiple groups or packages, or at multiple locations.

[0049] As used herein, the term "or" may be interpreted in an inclusive or exclusive sense. Additionally, descriptions of resources, operations, or structures in the singular should not be read to exclude the plural. Conditional language, such as "can," "could," "might," or "may," among others, is generally intended to convey that certain embodiments include certain features, elements, and / or steps, but other embodiments do not, unless otherwise stated or understood otherwise within the context in which it is used.

[0050] It should be noted that terms such as "optimize", "optimal", etc., as used herein, can be used to mean to create or achieve the most effective or perfect performance possible. However, as one of ordinary skill in the art reading this document will recognize, perfection is not always achieved. Thus, these terms can also encompass creating or achieving as good or effective or practical performance as possible under given circumstances, or creating or achieving better performance than could be achieved with other settings or parameters.

[0051] Moreover, various embodiments described herein are described with reference to exemplary block diagrams, flow charts, and other diagrams. As will become apparent to one of ordinary skill in the art after reading this specification, the illustrated embodiments and their various alternatives can be implemented without being limited to the illustrated examples. For example, block diagrams and their accompanying description should not be construed as mandating a particular architecture or configuration. DISCLOSURE OF THEINVENTION (Item 1) 2.5-4.0 wt% Ag; 0.4-0.8 wt% Cu; 5.0-9.0 wt% Sb; 1.5-3.5 wt% Bi; 0.05 to 0.35 wt.% Ni; and remainder Sn; Solder alloys containing (Item 2) 2. The solder alloy according to item 1, further comprising 0.1 to 3.0 wt. % In. (Item 3) 2. The solder alloy according to item 1, wherein the solder alloy essentially consists of 3.0-4.0 wt. % Ag, 0.5-0.7 wt. % Cu, 5.0-6.0 wt. % Sb, 2.5-3.5 wt. % Bi, 0.1-0.2 wt. % Ni, and the balance Sn. (Item 4) 3. The solder alloy according to item 2, wherein the solder alloy essentially consists of 3.0 to 4.0 wt. % Ag, 0.5 to 0.7 wt. % Cu, 5.0 to 6.0 wt. % Sb, 2.5 to 3.5 wt. % Bi, 0.3 to 0.6 wt. % In, 0.1 to 0.2 wt. % Ni, and the balance Sn. (Item 5) Flux; and 2.5-4.0 wt% Ag; 0.4-0.8 wt% Cu; 5.0-9.0 wt% Sb; 2.8-5.0 wt% Bi; 0.05 to 0.35 wt.% Ni; and remainder Sn; A solder alloy powder comprising: Contains solder paste. (Item 6) 6. The solder paste according to item 5, wherein the solder alloy further contains 0.1 to 3.0 wt. % In. (Item 7) 6. The solder paste according to item 5, wherein the solder alloy essentially consists of 3.0 to 4.0 wt. % Ag, 0.5 to 0.7 wt. % Cu, 5.0 to 6.0 wt. % Sb, 2.5 to 3.5 wt. % Bi, 0.1 to 0.2 wt. % Ni, and the balance Sn. (Item 8) 6. The solder paste according to item 5, wherein the solder alloy essentially consists of 3.0 to 4.0 wt. % Ag, 0.5 to 0.7 wt. % Cu, 5.0 to 6.0 wt. % Sb, 2.5 to 3.5 wt. % Bi, 0.3 to 0.6 wt. % In, 0.1 to 0.2 wt. % Ni, and the balance Sn. (Item 9) a main ceramic body; and a side on which the electrodes and thermal pads are located; A part comprising: Copper substrate and; a solder alloy electrically coupling the component and the copper substrate; An apparatus comprising: The solder alloy is 2.5-4.0 wt% Ag; 0.4-0.8 wt% Cu; 5.0-9.0 wt% Sb; 1.5-3.5 wt% Bi; 0.05 to 0.35 wt.% Ni; and remainder Sn; An apparatus comprising: (Item 10) 10. The apparatus of claim 9, wherein the solder alloy further comprises 0.1 to 3.0 wt. % In. (Item 11) 10. The apparatus of claim 9, wherein the solder alloy consists essentially of 3.0-4.0 wt. % Ag, 0.5-0.7 wt. % Cu, 5.0-6.0 wt. % Sb, 2.5-3.5 wt. % Bi, 0.1-0.2 wt. % Ni, and the balance Sn. (Item 12) Item 12. The apparatus of item 11, wherein the solder alloy consists essentially of 3.0-4.0 wt. % Ag, 0.5-0.7 wt. % Cu, 5.0-6.0 wt. % Sb, 2.5-3.5 wt. % Bi, 0.3-0.6 wt. % In, 0.1-0.2 wt. % Ni, and the balance Sn. (Item 13) 5. An LED module in which an LED component is assembled using the solder alloy according to any one of items 1 to 4. (Item 14) Light emitting diode (LED) components; Metal Core Printed Circuit Boards (MCPCBs); a solder alloy that electrically couples the LED component and the MCPCB; An apparatus comprising: The solder alloy is 2.5-4.0 wt% Ag; 0.4-0.8 wt% Cu; 5.0-9.0 wt% Sb; 1.5-3.5 wt% Bi; 0.05 to 0.35 wt.% Ni; and remainder Sn; An apparatus comprising: (Item 15) 10. The apparatus of claim 9, wherein the solder alloy further comprises 0.1 to 3.0 wt. % In. (Item 16) 10. The apparatus of claim 9, wherein the solder alloy consists essentially of 3.0-4.0 wt. % Ag, 0.5-0.7 wt. % Cu, 5.0-6.0 wt. % Sb, 2.5-3.5 wt. % Bi, 0.1-0.2 wt. % Ni, and the balance Sn. (Item 17) Item 12. The apparatus of item 11, wherein the solder alloy consists essentially of 3.0-4.0 wt. % Ag, 0.5-0.7 wt. % Cu, 5.0-6.0 wt. % Sb, 2.5-3.5 wt. % Bi, 0.3-0.6 wt. % In, 0.1-0.2 wt. % Ni, and the balance Sn.

Claims

1. 2.5-4.0 wt.% Ag; 0.4-0.8 wt.% Cu; More than 5.0 wt.% and not more than 9.0 wt.% Sb; 2.8 to 3.5 wt.% Bi; 0.05 to 0.35 wt.% Ni; 0.1 to 3.0 wt. % In; and Remainder Sn; A solder alloy consisting of

2. %. The solder alloy of claim 1, wherein the solder alloy comprises 3.0-4.0 wt. % Ag, 0.5-0.7 wt. % Cu, greater than 5.0 wt. % and up to 6.0 wt. % Sb, 2.8-3.5 wt. % Bi, 0.3-0.6 wt. % In, 0.1-0.2 wt. % Ni, and the balance Sn.

3. Flux; and 2.5-4.0 wt.% Ag; 0.4-0.8 wt.% Cu; More than 5.0 wt.% and not more than 9.0 wt.% Sb; 2.8 to 3.5 wt.% Bi; 0.05 to 0.35 wt.% Ni; 0.1 to 3.0 wt. % In; and Remainder Sn; A solder alloy powder consisting of: Contains solder paste.

4. 4. The solder alloy powder according to claim 3, comprising 3.0 to 4.0 wt. % Ag, 0.5 to 0.7 wt. % Cu, more than 5.0 wt. % and not more than 6.0 wt. % Sb, 2.8 to 3.5 wt. % Bi, 0.3 to 0.6 wt. % In, 0.1 to 0.2 wt. % Ni, and the balance Sn. Solder paste according to claim 3.

5. a main ceramic body; and a surface on which the electrodes and thermal pads are disposed; A part comprising: A copper substrate; a solder alloy electrically coupling the component and the copper substrate; An apparatus comprising: The solder alloy is 2.5-4.0 wt.% Ag; 0.4-0.8 wt.% Cu; More than 5.0 wt.% and not more than 9.0 wt.% Sb; 2.8 to 3.5 wt.% Bi; 0.05 to 0.35 wt.% Ni; 0.1 to 3.0 wt. % In; and Remainder Sn; An apparatus comprising:

6. 6. The apparatus of claim 5, wherein the solder alloy consists of 3.0-4.0 wt.% Ag, 0.5-0.7 wt.% Cu, greater than 5.0 wt.% and up to 6.0 wt.% Sb, 2.8-3.5 wt.% Bi, 0.3-0.6 wt.% In, 0.1-0.2 wt.% Ni, and balance Sn.

7. A light emitting diode (LED) component; A metal core printed circuit board (MCPCB); a solder alloy that electrically couples the LED component and the MCPCB; An apparatus comprising: The solder alloy is 2.5-4.0 wt.% Ag; 0.4-0.8 wt.% Cu; More than 5.0 wt.% and not more than 9.0 wt.% Sb; 2.8 to 3.5 wt.% Bi; 0.05 to 0.35 wt.% Ni; 0.1 to 3.0 wt. % In; and Remainder Sn; An apparatus comprising:

8. 8. The apparatus of claim 7, wherein the solder alloy consists of 3.0-4.0 wt.% Ag, 0.5-0.7 wt.% Cu, greater than 5.0 wt.% and up to 6.0 wt.% Sb, 2.8-3.5 wt.% Bi, 0.3-0.6 wt.% In, 0.1-0.2 wt.% Ni, and balance Sn.

9. 2. The solder alloy of claim 1, wherein the solder alloy consists of 3.0-4.0 wt.% Ag, 0.5-0.7 wt.% Cu, 5.5 wt.% Sb, 2.8-3.5 wt.% Bi, 0.05-0.35 wt.% Ni, 0.3-0.6 wt.% In, and the balance Sn.

10. 10. The solder alloy of claim 9, wherein the solder alloy consists of 3.0-4.0 wt.% Ag, 0.5-0.7 wt.% Cu, 5.5 wt.% Sb, 3.2 wt.% Bi, 0.05-0.35 wt.% Ni, 0.3-0.6 wt.% In, and the balance Sn.

11. 11. The solder alloy of claim 10, wherein the solder alloy consists of 3.2 wt.% Ag, 0.7 wt.% Cu, 5.5 wt.% Sb, 3.2 wt.% Bi, 0.5 wt.% In, 0.2 wt.% Ni, and balance Sn.

12. 11. The solder alloy of claim 10, wherein the solder alloy consists of 3.2 wt.% Ag, 0.7 wt.% Cu, 5.5 wt.% Sb, 3.2 wt.% Bi, 0.5 wt.% In, 0.3 wt.% Ni, and the balance Sn.

13. 2. The solder alloy of claim 1, wherein the solder alloy consists of 3.2 wt.% Ag, 0.7 wt.% Cu, 5.5 wt.% Sb, 3.2 wt.% Bi, 0.1 wt.% In, 0.1 wt.% Ni, and the balance Sn.

14. A solder alloy consisting of 3.0-4.0 wt. % Ag, 0.5-0.7 wt. % Cu, 5.0-6.0 wt. % Sb, 3.2 wt. % Bi, 0.05-0.35 wt. % Ni, 0.3-0.6 wt. % In, and the balance Sn.

15. 15. The solder alloy of claim 14, wherein the solder alloy consists of 3.0-4.0 wt.% Ag, 0.5-0.7 wt.% Cu, 5.0-6.0 wt.% Sb, 3.2 wt.% Bi, 0.05-0.35 wt.% Ni, 0.5 wt.% In, and the balance Sn.

16. 4. The solder paste of claim 3, wherein the solder alloy powder is composed of 3.0-4.0 wt. % Ag, 0.5-0.7 wt. % Cu, 5.5 wt. % Sb, 3.2 wt. % Bi, 0.05-0.35 wt. % Ni, 0.3-0.6 wt. % In, and the balance Sn.

17. 6. The apparatus of claim 5, wherein the solder alloy consists of 3.0-4.0 wt.% Ag, 0.5-0.7 wt.% Cu, 5.5 wt.% Sb, 2.8-3.5 wt.% Bi, 0.05-0.35 wt.% Ni, 0.3-0.6 wt.% In, and the balance Sn.

18. 6. The apparatus of claim 5, wherein the solder alloy consists of 3.0-4.0 wt.% Ag, 0.5-0.7 wt.% Cu, greater than 5.0 wt.% and up to 6.0 wt.% Sb, 3.2 wt.% Bi, 0.05-0.35 wt.% Ni, 0.3-0.6 wt.% In, and balance Sn.

19. 8. The apparatus of claim 7, wherein the solder alloy consists of 3.0-4.0 wt.% Ag, 0.5-0.7 wt.% Cu, 5.5 wt.% Sb, 2.8-3.5 wt.% Bi, 0.05-0.35 wt.% Ni, 0.3-0.6 wt.% In, and balance Sn.

20. 8. The apparatus of claim 7, wherein the solder alloy consists of 3.0-4.0 wt.% Ag, 0.5-0.7 wt.% Cu, greater than 5.0 wt.% and up to 6.0 wt.% Sb, 3.2 wt.% Bi, 0.05-0.35 wt.% Ni, 0.3-0.6 wt.% In, and balance Sn.

Citation Information

Patent Citations

  • Method of manufacturing light-emitting device

    JP2012169653A

  • Solder alloy

    JP2014057974A

  • Method for manufacturing solder joint structure, solder joint structure and soldering method

    JP2015225938A

  • Lead-free solder alloy, electronic circuit board, and electronic control device

    JP2016179498A

  • Method for manufacturing metal base substrate, method for manufacturing semiconductor device, metal base substrate, and semiconductor device

    JP2018056397A